2022
DOI: 10.1007/s00464-022-09097-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health-care utilization and expenditures for minimally invasive vs. open colectomy for benign disease

Abstract: Background Adoption of minimally invasive approaches continues to increase, and there is a need to reassess outcomes and cost. We aimed to compare open versus minimally invasive colectomy short- and long-term health-care utilization and payer/patient expenditures for benign disease. Methods This is a retrospective analysis of IBM® MarketScan® Database patients who underwent left or right colectomy for benign disease between 2013 and 2018. Outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…As has been demonstrated by other investigators, the MIS group demonstrated a lower perioperative complication rate compared to OS [ 6 , 10 , 15 ]. Health-care expenditure at 30-day post-discharge is shown in Supplementary Table 4.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…As has been demonstrated by other investigators, the MIS group demonstrated a lower perioperative complication rate compared to OS [ 6 , 10 , 15 ]. Health-care expenditure at 30-day post-discharge is shown in Supplementary Table 4.…”
Section: Discussionsupporting
confidence: 71%
“…To minimize the effect of potential confounding factors without reducing the sample size, we performed inverse probability of treatment weighting (IPTW) with stabilized weights [ 12 ]. Propensity score weights were calculated from logistic regression models with all the baseline patient factors mentioned above except for DRG as covariates based on prior knowledge and literature [ 10 , 13 , 14 ]. After IPTW, covariates were considered balanced if the absolute value of the standardized mean difference (SMD) was less than 0.1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) after excluding duplicates. Twenty-one studies were excluded [18][19][20][21][22][23][24][25][26][27][28][36][37][38][39][40][41][42][43][44][45][46]. The reasons for exclusion were cohort with less than 20 RLC cases [25,[41][42][43][44][45][46], impossibility to extract data on RLC [18][19][20][21][22][23][24][36][37][38][39][40] or data overlap [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies were excluded [18][19][20][21][22][23][24][25][26][27][28][36][37][38][39][40][41][42][43][44][45][46]. The reasons for exclusion were cohort with less than 20 RLC cases [25,[41][42][43][44][45][46], impossibility to extract data on RLC [18][19][20][21][22][23][24][36][37][38][39][40] or data overlap [26][27][28]. Eleven studies published between 2013 and 2022 were considered eligible for data extraction and were therefore included in the meta-analysis [6][7][8][9][10]…”
Section: Resultsmentioning
confidence: 99%